2021
DOI: 10.1002/mnfr.202000945
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Carcinogenic Risk Attached to Vitamin B12 Deficient Diets and What Should We Do About It? Reviewing the Facts

Abstract: The number of individuals partaking in veganism has increased sharply in the last decade. Therefore, it is critical to look at the implications of vegan diets for public health. Although there are multiple health benefits of a vegan diet, studies have also linked the diet with deficiencies in various micronutrients. This study focuses on vitamin B12, because of its critical role in DNA synthesis and methylation. In light of these connections, a critical review of recent scientific literature is conducted to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 93 publications
(150 reference statements)
1
3
0
Order By: Relevance
“…Miranti in 2017 [ 18 ] also identified an increased risk of developing cancer up to 5.8 times more than the control when patients had a low vitamin B12 concentration, presuming that the low intake of this vitamin would be due to an initial gastritis, for example, since, for satisfactory absorption, an intact gastric mucosa is required to produce acid and intrinsic factor. Corroborating our finding, Loedin and Speijer highlight that B12 deficiency enhances the incorrect incorporation of uracil into the genetic code, leading to impaired DNA synthesis and increasing genomic instability [ 19 ]. Furthermore, it is known that low levels of Vitamin B12 are also associated with global DNA hypomethylation, a known hallmark of early carcinogenesis [ 20 ].…”
Section: Discussionsupporting
confidence: 62%
“…Miranti in 2017 [ 18 ] also identified an increased risk of developing cancer up to 5.8 times more than the control when patients had a low vitamin B12 concentration, presuming that the low intake of this vitamin would be due to an initial gastritis, for example, since, for satisfactory absorption, an intact gastric mucosa is required to produce acid and intrinsic factor. Corroborating our finding, Loedin and Speijer highlight that B12 deficiency enhances the incorrect incorporation of uracil into the genetic code, leading to impaired DNA synthesis and increasing genomic instability [ 19 ]. Furthermore, it is known that low levels of Vitamin B12 are also associated with global DNA hypomethylation, a known hallmark of early carcinogenesis [ 20 ].…”
Section: Discussionsupporting
confidence: 62%
“…Global hypomethylation of DNA is a characteristic of early carcinogenesis. Thus, if not adequately replaced, VD may inadvertently lead to cancers [ 20 ]. Wu et al found that blood B12 levels were substantially lower in menopausal and postmenopausal breast cancer patients, and patients with the lowest B12 levels had an elevated risk of breast cancer [ 21 ].…”
Section: Reviewmentioning
confidence: 99%
“…Deficiencies in essential nutrients like folate [134,135], vitamin B12 [136], and iron [137], which function as critical cellular substrates and cofactors, can impair the function of enzymes involved in histone acylation, leading to abnormal histone modifications and potentially promoting oncogenesis. Altered metabolite levels and imbalanced nutrient utilization can also affect the activity of HATs and HDACs, which regulate histone acylation.…”
Section: The Role Of Dietary and Metabolism-derived Histone Acylation...mentioning
confidence: 99%